Battery diaphragm, preparation method thereof and battery
By using non-fluorine composite materials and adhesive materials in lithium battery separators to control the thickness and particle size ratio of the cladding layer, the problem of difference in adhesion of lithium battery separators at low and high temperatures is solved, and the stability of the battery cell preparation process and the improvement of battery performance is achieved.
Patent Information
- Application Number
- CN202411742744.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
The adhesion of the existing lithium battery separators with the electrode sheet at low and high temperatures is quite different, resulting in the battery cell performance being affected after the battery cell preparation process goes from hot pressing to cold pressing.
The battery separator is prepared using non-fluorine composite materials and adhesive materials. By controlling the relationship between the thickness of the coating layer and the particle size of the unit material, and the glass transition temperature Y of the first and second polymers, the adhesiveness of the separator is ensured to be consistent at low and high temperatures.
The high adhesion between the battery separator and the electrode sheet at low and high temperatures is achieved, ensuring that the battery cell preparation process from hot pressing to cold pressing does not affect the overall performance of the battery cell, and improving the cycle stability and safety performance of the battery.
Smart Images

Figure CN119581793A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery separator and a preparation method thereof, and a battery. Background Art
[0002] As an important component of the battery, the lithium battery separator can block the passage of electrons and allow the passage of ions. It plays a role in blocking the positive and negative electrodes in the battery, preventing the positive and negative electrodes from contacting and short-circuiting, causing the battery to catch fire, explode, and other dangers. The bare base film has no bonding effect with the electrode sheet. Therefore, if the bare base film is used alone as a separator barrier for the positive and negative electrodes, the battery cell will be soft and have no hardness, which will make installation difficult. Therefore, a layer of glue, often a PVDF glue layer, needs to be coated on the surface of the separator. For example, patent number CN105552277A uses an aqueous system instead of an oily system to coat a layer of 0.1-0.5μm uniform PVDF spherical particles on the lithium battery separator, which improves the adhesion between the electrode sheet and the separator, thereby improving the overall hardness of the battery. Since non-fluorine adhesives have an amorphous structure, they are better than PVDF in bonding to the electrode sheet. The existing market demand for non-fluorine separators is growing. In addition, in order to reduce costs and energy consumption, the winding or stacking of diaphragms and pole pieces in the battery cell preparation process has gradually changed from hot pressing to cold pressing. However, the cold pressing process will inevitably reduce the adhesion between the diaphragm and the pole piece, which will cause the battery cell to open easily and affect the overall battery cell performance.
[0003] Therefore, it is necessary to find a non-fluorine adhesive that has high adhesion to the electrode at low and high temperatures, to ensure that the adhesion between the low-temperature and high-temperature diaphragms and the electrode is not much different, thereby ensuring that the battery cell preparation process from hot pressing to cold pressing does not affect the overall performance of the battery cell.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One object of the present invention is to provide a battery separator comprising a non-fluorine composite material and an adhesive material, so that the separator and the pole piece have high adhesion at low and high temperatures, ensuring that the adhesion between the low-temperature and high-temperature separators and the pole pieces is not much different, thereby ensuring that the preparation of the battery cell from hot pressing to cold pressing does not affect the overall performance of the battery cell.
[0006] Another object of the present invention is to provide a method for preparing a battery separator, which is simple, easy to operate and environmentally friendly.
[0007] Another object of the present invention is to provide a battery.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A battery separator comprises a substrate layer and a discontinuous dot coating located on at least one side of the substrate layer; the dot coating comprises a non-fluorine composite material and an adhesive material; the non-fluorine composite material comprises an aggregate of several unit materials, the unit material comprises a substrate and a coating layer located on the surface of the substrate, the substrate comprises a first polymer, and the coating layer comprises a second polymer; the ratio η of the thickness of the coating layer to the particle size of the unit material and the glass transition temperature Y of the second polymer satisfy the relationship: Y=100η-46, wherein η is 25% to 46%; the difference between the glass transition temperature X of the first polymer and the glass transition temperature Y of the second polymer satisfies: XY≥95°C.
[0010] In some embodiments, among the dot coatings, any dot coating with a particle size greater than 100 μm is defined as a Q coating, the dot coating with the shortest distance to the Q coating is defined as an M coating, and the distance L between the Q coating and the M coating satisfies: 100 μm≤L≤350 μm.
[0011] In some embodiments, the difference between the glass transition temperature X of the first polymer and the glass transition temperature Y of the second polymer satisfies: 95°C≤XY≤125°C.
[0012] In some embodiments, the particle size D50 of the non-fluorine composite material is 4 to 6 μm.
[0013] In some embodiments, the particle size D50 of the unit material is between 0.40 and 0.60 μm.
[0014] In some embodiments, the first polymerized monomer of the first polymer includes one or more of methyl methacrylate, methacrylonitrile, 2-ethylhexyl methacrylate, methacrylonitrile, ethyl methacrylate, butyl methacrylate, styrene and acrylonitrile.
[0015] In some embodiments, the second polymerizable monomer of the second polymer includes one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, 1-butene, isooctyl acrylate, butyl methacrylate and 2-ethylhexyl acrylate.
[0016] In some embodiments, the mass ratio of the non-fluorine composite material to the adhesive material is 100:(3-8).
[0017] In some embodiments, the adhesive material includes at least one of styrene-butadiene rubber, polyacrylate, polystyrene, polymethyl styrene, polyacrylonitrile and epoxy resin.
[0018] In some embodiments, the dot coating further includes a stabilizer; the mass ratio of the non-fluorine composite material, the adhesive material and the stabilizer is 100:(3-8):(0.3-0.8).
[0019] In some embodiments, the coverage of the dot coating on the surface of the substrate layer is 10% to 20%.
[0020] In some embodiments, the bonding strength between the battery separator and the electrode sheet under the conditions of 5 MPa, 26°C, and cold pressing for 3 min is F1, and the bonding strength between the battery separator and the electrode sheet under the conditions of 5 MPa, 80°C, and hot pressing for 3 min is F2, and F1 and F2 satisfy the relationship: (F2-F1) / F1<20%.
[0021] The method for preparing the battery separator as described above comprises the following steps:
[0022] The non-fluorine composite material emulsion and the adhesive material are mixed to obtain a mixed slurry; the mixed slurry is coated on at least one side surface of the substrate layer to form a discontinuous dot coating, and the battery separator is obtained after drying.
[0023] In some embodiments, the method for preparing the non-fluorine composite material emulsion comprises the following steps:
[0024] A first emulsifier, a first polymerizable monomer, a first initiator and a first solvent are subjected to a first polymerization reaction to obtain a first system containing matrix particles; the first system and a second solvent are mixed and subjected to a first ultraviolet irradiation, and then mixed with a second system, a second polymerizable monomer and a second initiator and subjected to a second polymerization reaction to obtain a second system containing unit materials; the second system is mixed with salts and subjected to a second ultraviolet irradiation, and then mixed with a second initiator to obtain an emulsion containing the non-fluorine composite material.
[0025] In some embodiments, the first polymerization reaction specifically includes: pre-mixing a portion of the first emulsifier, a portion of the first polymerization monomer, a portion of the first initiator and a portion of the first solvent, and then adding the remaining first emulsifier, first polymerization monomer, first initiator and first solvent for polymerization reaction.
[0026] In some embodiments, the first ultraviolet irradiation time is 20 to 40 minutes.
[0027] In some embodiments, the second external irradiation time is 5 to 15 minutes.
[0028] In some embodiments, the mixed slurry further includes a stabilizer.
[0029] A battery comprises the battery separator.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The battery separator of the present invention comprises a non-fluorine composite material and an adhesive material. The non-fluorine composite material can make the adhesion between the separator and the electrode sheet at low temperature and high temperature not much different by satisfying the relationship limitation. After the battery cell preparation process is changed from hot pressing to cold pressing, it has little effect on the overall performance of the battery cell, which is beneficial to ensure the cycle stability and safety performance of the battery.
[0032] (2) The battery separator of the present invention controls the distance L between the Q coating and the M coating to satisfy 100 μm ≤ L ≤ 350 μm, which is beneficial to improving the comprehensive performance of the separator. The coating has good overall air permeability, the separator has strong adhesion to the electrode, and the difference in adhesion between high temperature and low temperature is not large. After being made into a battery cell, it is not easy to bulge, and the coated separator has good ionic conductivity.
[0033] (3) The preparation method of the battery separator of the present invention is simple, easy and environmentally friendly. In the preparation method of the non-fluorine composite material, the first UV irradiation is used to generate free radicals on the surface of the matrix particles, which is conducive to the tight coating of the coating layer and the coating thickness of the coating layer. The second UV irradiation is conducive to controlling the agglomeration effect of the unit material and the particle size of the non-fluorine composite material, so that the ratio η of the coating layer thickness to the unit material particle size and the glass transition temperature Y of the second polymer satisfy the relationship Y=100η-46.
[0034] (4) The battery of the present invention has excellent cycle performance and high safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is a schematic diagram of the structure of the non-fluorine composite material of the present invention;
[0037] Figure 2 is a schematic diagram of a battery separator of the present invention;
[0038] Figure 3 is a transmission electron microscope image of the non-fluorine composite material in Example 1 of the present invention;
[0039] Figure 4 is a test curve of the glass transition temperature of the substrate in Example 1 of the present invention;
[0040] Figure 5This is a test curve of the glass transition temperature of the non-fluorine composite material in Example 1 of the present invention.
[0041] Reference numerals:
[0042] 1-unit material, 101-substrate, 102-coating layer, 2-dot coating, 3-substrate layer. DETAILED DESCRIPTION
[0043] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0044] According to one aspect of the present invention, the present invention relates to a battery separator, comprising a substrate layer and a discontinuous dot coating located on at least one side of the substrate layer; the dot coating comprises a non-fluorine composite material and an adhesive material; the non-fluorine composite material comprises agglomerates of several unit materials, the unit material comprises a substrate and a coating layer located on the surface of the substrate, the substrate comprises a first polymer, and the coating layer comprises a second polymer; the ratio η of the thickness of the coating layer to the particle size of the unit material and the glass transition temperature Y of the second polymer satisfy the relationship: Y=100η-46, wherein η is 25% to 46%; the difference between the glass transition temperature X of the first polymer and the glass transition temperature Y of the second polymer satisfies: XY≥95°C.
[0045] The non-continuous dot coating in the battery separator of the present invention comprises a non-fluorine composite material and an adhesive material, wherein the non-fluorine composite material can make the adhesion between the separator and the electrode sheet at low temperature and high temperature not much different by satisfying the relationship limitation, and the overall performance of the battery cell is not greatly affected after the battery cell preparation process is changed from hot pressing to cold pressing, which is beneficial to ensuring the cycle stability and safety performance of the battery.
[0046] In some embodiments, the value of η includes but is not limited to 25%, 30%, 32%, 35%, 38%, 40%, 42% or 46%, etc.
[0047] In some embodiments, the value of XY is 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 121°C, 122°C, 123°C, 125°C, 128°C, etc. In some embodiments, the difference between the glass transition temperature X of the first polymer and the glass transition temperature Y of the second polymer satisfies: 115°C≤XY≤125°C;
[0048] In some embodiments, in the dot coating, any dot coating with a particle size greater than 100 μm is defined as a Q coating, and the dot coating with the shortest distance from the Q coating is defined as an M coating, and the distance L between the Q coating and the M coating satisfies: 100 μm ≤ L ≤ 350 μm. In some embodiments, the distance L between the Q coating and the M coating is 100 μm, 150 μm, 180 μm, 200 μm, 250 μm, 300 μm or 350 μm, etc. The battery diaphragm of the present invention comprises the above-mentioned non-fluorine composite material, and the distance L between the Q coating and the M coating is controlled to meet the above-mentioned range, which is beneficial to improving the comprehensive performance of the diaphragm. The coating has good overall air permeability, the diaphragm has strong adhesion to the pole piece, and the difference in high temperature and low temperature adhesion is not large. After being made into a battery cell, it is not easy to bulge, and the coated diaphragm has good ionic conductivity.
[0049] In some embodiments, the particle size D50 of the non-fluorine composite material is 4 to 6 μm, for example, 4 μm, 4.3 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.
[0050] In some embodiments, the particle size D50 of the unit material is between 0.40 and 0.60 μm, for example, 0.4 μm, 0.45 μm, 0.48 μm, 0.5 μm, 0.52 μm, 0.55 μm, 0.6 μm, etc.
[0051] In some embodiments, the first polymerizable monomer of the first polymer includes one or more of methyl methacrylate, methacrylonitrile, 2-ethylhexyl methacrylate, methacrylonitrile, ethyl methacrylate, butyl methacrylate, styrene and acrylonitrile, such as a combination of methacrylonitrile and 2-ethylhexyl methacrylate, a combination of 2-ethylhexyl methacrylate and methacrylonitrile, etc.
[0052] In some embodiments, the second polymerizable monomer of the second polymer includes one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, 1-butene, isooctyl acrylate, butyl methacrylate and 2-ethylhexyl acrylate, for example, a combination of 1-butene and ethyl acrylate, a combination of 1-butene and 2-ethylhexyl acrylate, etc.
[0053] In some embodiments, the mass ratio of the non-fluorine composite material to the adhesive material is 100:(3-8), such as 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, etc. In some embodiments, the adhesive material includes at least one of styrene-butadiene rubber, polyacrylate, polystyrene, polymethyl styrene, polyacrylonitrile and epoxy resin. The non-fluorine composite material and the adhesive material have a suitable mass ratio, which is conducive to coordinated play, so that the difference in adhesion between the diaphragm and the electrode sheet at low temperature and high temperature is not large, and the comprehensive performance of the battery diaphragm is improved.
[0054] In some embodiments, the dot coating further includes a stabilizer; the stabilizer includes one or more of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, methyl hydroxyethyl cellulose and sodium carboxymethyl acrylate. The mass ratio of the non-fluorine composite material, the adhesive material and the stabilizer is 100:(3-8):(0.3-0.8), for example, 100:3:0.3, 100:4:0.4, 100:5:0.6, 100:7:0.7, 100:8:0.8, etc. The non-fluorine composite material, the adhesive material and the stabilizer adopt an appropriate mass ratio, which is more conducive to ensuring the comprehensive performance of the battery separator.
[0055] In some embodiments, the coverage of the dot coating on the surface of the substrate layer is 10% to 20%, such as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0056] In some embodiments, the bonding strength between the battery separator and the electrode sheet under the conditions of 5 MPa, 26°C, and cold pressing for 3 min is F1, and the bonding strength between the battery separator and the electrode sheet under the conditions of 5 MPa, 80°C, and hot pressing for 3 min is F2, and F1 and F2 satisfy the relationship: (F2-F1) / F1<20%, and the value of (F2-F1) / F1 is 1%, 3%, 4%, 5%, 7%, 8%, 10%, 12%, 15% or 19%, etc.
[0057] In some embodiments, the substrate layer includes a single-layer PP film, a single-layer PE film, a double-layer PE / PP composite film or a double-layer PP / PP composite film. The thickness of the substrate layer is 5 to 16 μm, such as 5 μm, 10 μm, 16 μm, etc.
[0058] According to another aspect of the present invention, the present invention also relates to a method for preparing the battery separator, comprising the following steps:
[0059] The non-fluorine composite material emulsion and the adhesive material are mixed to obtain a mixed slurry; the mixed slurry is coated on at least one side surface of the substrate layer to form a discontinuous dot coating, and the battery separator is obtained after drying.
[0060] The preparation method of the battery separator of the present invention is simple, easy to operate and environmentally friendly.
[0061] The preparation method of the battery separator of the present invention controls the distance L between the Q coating and the M coating to satisfy 100μm≤L≤350μm, which is beneficial to improving the comprehensive performance of the separator. The coating has good overall air permeability, the separator has strong adhesion to the electrode, and the difference in high-temperature and low-temperature adhesion is not large. After the battery cell is made, it is not easy to bulge, and the coated separator has good ionic conductivity.
[0062] The method for preparing the non-fluorine composite material emulsion as described above comprises the following steps:
[0063] A first emulsifier, a first polymerizable monomer, a first emulsifier and a first solvent are subjected to a first polymerization reaction to obtain a first system containing matrix particles; the first system and a second solvent are mixed and subjected to a first ultraviolet irradiation, and then mixed with a second system, a second polymerizable monomer and a second initiator to conduct a second polymerization reaction to obtain a second system containing unit materials; the second system is mixed with salts and subjected to a second ultraviolet irradiation, and then mixed with a second initiator to obtain an emulsion containing the non-fluorine composite material.
[0064] The preparation method of the non-fluorine composite material of the present invention uses the first UV irradiation to generate free radicals on the surface of the matrix particles, which is beneficial to the tight coating of the coating layer and the control of the coating thickness of the coating layer. The second ultraviolet irradiation is beneficial to control the agglomeration effect of the unit material and the particle size of the non-fluorine composite material, so that the ratio η of the coating layer thickness to the unit material particle size and the glass transition temperature Y of the second polymer satisfy the relationship Y=100η-46.
[0065] In some embodiments, the first polymerization reaction specifically includes: pre-mixing a portion of the first emulsifier, a portion of the first polymerization monomer, a portion of the first initiator and a portion of the first solvent, and then adding the remaining first emulsifier, first polymerization monomer, first initiator and first solvent for polymerization reaction.
[0066] In some embodiments, the first ultraviolet irradiation time is 20 to 40 minutes, and the flow time is 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, etc.
[0067] In some embodiments, the second external irradiation time is 5 to 15 minutes, such as 5 minutes, 8 minutes, 10 minutes, 12 minutes or 15 minutes.
[0068] In some embodiments, the fixed wavelengths of the first ultraviolet irradiation and the second external irradiation are independently 150-450 nm, such as 150 nm, 200 nm, 250 nm, 300 nm, 400 nm, 500 nm, etc. The powers are independently 50-300 W / cm, such as 50 W / cm, 100 W / cm, 150 W / cm, 200 W / cm, 250 W / cm or 300 W / cm, etc. In some specific embodiments of the present invention, the fixed wavelengths of the first ultraviolet irradiation and the second external irradiation are 210 nm, and the powers are independently 135 W / cm.
[0069] In a preferred embodiment, the method for preparing the non-fluorine composite material comprises the following steps:
[0070] (a) Premixing part of the first emulsifier, part of the first polymerization monomer, part of the first initiator and part of the first solvent, introducing a protective gas (such as nitrogen), heating and pressurizing (heating to 70-80° C., pressurizing to 2-4 MPa), reacting for 1-4 hours, reducing the pressure to room pressure, adding the remaining first emulsifier, first polymerization monomer, first initiator and first solvent, heating to 70-80° C., pressurizing to 2-3.5 MPa, and performing a polymerization reaction to obtain a first system containing matrix particles.
[0071] (b) After mixing the first system and the second solvent, subjecting the mixture to a first ultraviolet irradiation for 20 to 40 minutes, adding the second system and mixing with the second polymerization monomer and the second initiator, heating to (75 to 85° C.), stirring, and cooling to room temperature after the reaction is complete to obtain a second system containing unit materials.
[0072] (c) After mixing the second system with the salt, subjecting the mixture to a second ultraviolet irradiation for 5 to 15 minutes, adding a second initiator, controlling the stirring speed to 300 to 400 rpm, and stirring for 1 to 3 hours to obtain the non-fluorine composite material.
[0073] In some embodiments, the first emulsifier and the second emulsifier each independently comprise sodium lauryl sulfate.
[0074] In some embodiments, the first solvent and the second solvent each independently include water, such as deionized water.
[0075] In some embodiments, the first initiator and the second initiator each independently comprise sodium persulfate.
[0076] In some embodiments, the mixed slurry further includes a stabilizer.
[0077] In some embodiments, a method for preparing a battery separator includes: taking a non-fluorine composite material emulsion, adding a bonding material and a stabilizer, stirring evenly, and spraying the mixed slurry on the surface of the substrate layer by spraying, adjusting the spraying flow rate and the rotor rotation speed.
[0078] According to another aspect of the present invention, the present invention also relates to a battery comprising the battery separator.
[0079] The battery of the present invention has high capacity retention rate, good cycle stability and good safety performance.
[0080] In some embodiments, a battery includes the above-mentioned battery separator, a positive electrode sheet, a negative electrode sheet and an electrolyte.
[0081] The following is further explained in conjunction with specific embodiments and comparative examples.
[0082] Example 1
[0083] A method for preparing a non-fluorine composite material comprises the following steps:
[0084] (a) Add 200 parts of deionized water, 0.05 parts of sodium dodecyl sulfate, 0.1 parts of sodium persulfate and 10 parts of methacrylonitrile to a reactor, introduce nitrogen, heat to 78.0°C, pressurize to 3.0 MPa, react for 3 hours, reduce the pressure to room pressure, continue to add 200 parts of deionized water, 0.55 parts of sodium dodecyl sulfate, 0.7 parts of sodium persulfate and 70 parts of methacrylonitrile and 20 parts of 2-ethylhexyl methacrylate core monomer, heat to 78.0°C, pressurize to 3.0 MPa, carry out a first polymerization reaction, make the core particles continue to grow, and when the reaction is completed, obtain a first system containing matrix material particles.
[0085] (b) 500 parts of the first system and 400 parts of deionized water are slowly stirred in a reaction kettle, UV irradiation is started for 30 minutes to generate free radicals on the surface of the particles in the first system, 300 parts of 1-butene, 100 parts of 2-ethylhexyl methacrylate and 0.7 parts of sodium persulfate are added, and the mixture is heated to 80.0° C. and slowly stirred. After the reaction is complete, the mixture is cooled to room temperature to obtain a second system containing unit materials.
[0086] (c) Take 200 parts of the second system, stir, add 0.8 parts of 1.0 mol / L calcium nitrate solution, irradiate with UV for 10 minutes to generate a small amount of free radicals on the surface of the particles in the second system, add 0.01 parts of sodium persulfate, and then control the stirring speed to 350 rpm and the time for 2.5 hours. After the emulsion breaks and agglomerates, add water to dilute to 15% solid content to obtain a non-fluorine composite material emulsion. The schematic diagram of the non-fluorine composite material is shown in Figure 1As shown, it includes an agglomerate of several unit materials 1 , and the unit material 1 includes a matrix 101 and a coating layer 102 located on the surface of the matrix 101 .
[0087] A method for preparing a battery separator comprises: taking 100 parts of the non-fluorine composite material emulsion of the present embodiment, adding 0.08 parts of sodium carboxymethyl cellulose and 0.8 parts of polyacrylate, stirring evenly, and spraying the mixed slurry on the surface of a substrate layer 3 by spraying, adjusting the spraying flow rate and the rotor rotation speed to form a dot coating 2, wherein the substrate layer 3 is a PP film with a thickness of 8 μm.
[0088] After drying, the surface density is 0.55g / m 2 Battery separators,
[0089] Example 2
[0090] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0091] In step (a), the heating temperature was adjusted to 80.0°C and the pressurizing pressure was adjusted to 2.8 MPa.
[0092] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 194 parts and 40 parts respectively.
[0093] In step (c), the stirring speed was adjusted to 320 rpm and the stirring time was adjusted to 3.0 h.
[0094] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0095] Example 3
[0096] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0097] In step (a), the heating temperature was adjusted to 76.5° C. and the pressurizing pressure was adjusted to 2.8 MPa.
[0098] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 139 parts and 17 parts respectively.
[0099] In step (c), the stirring speed was adjusted to 360 rpm and the stirring time was adjusted to 2.0 h.
[0100] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0101] Example 4
[0102] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0103] In step (a), the heating temperature was adjusted to 76.0°C and the pressurizing pressure was adjusted to 3.5 MPa.
[0104] In step (b), 347 parts of 1-butene and 142 parts of 2-ethylhexyl methacrylate were used, respectively.
[0105] In step (c), the stirring speed was adjusted to 335 rpm and the stirring time was adjusted to 3.0 h.
[0106] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0107] Example 5
[0108] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0109] In step (a), the heating temperature was adjusted to 78.5°C and the pressurizing pressure was adjusted to 2.5 MPa.
[0110] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 167 parts and 27 parts respectively.
[0111] In step (c), the stirring speed was adjusted to 345 rpm and the stirring time was adjusted to 2.2 h.
[0112] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0113] Example 6
[0114] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0115] In step (a), the heating temperature was adjusted to 77.5°C and the pressurizing pressure was adjusted to 2.8 MPa.
[0116] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 237 parts and 63 parts respectively.
[0117] In step (c), the stirring speed was adjusted to 330 rpm and the stirring time was adjusted to 2.8 h.
[0118] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0119] Example 7
[0120] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0121] In step (a), the heating temperature was adjusted to 77.0°C and the pressurizing pressure was adjusted to 2.5 MPa.
[0122] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 269 parts and 85 parts respectively.
[0123] In step (c), the stirring speed was adjusted to 325 rpm and the stirring time was adjusted to 3.2 h.
[0124] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0125] Comparative Example 1
[0126] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0127] In step (a), the heating temperature was adjusted to 78.5° C. and the pressurizing pressure was adjusted to 2.6 MPa.
[0128] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 179 parts and 34 parts respectively.
[0129] In step (c), the stirring speed was adjusted to 328 rpm and the stirring time was adjusted to 2.5 h.
[0130] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0131] Comparative Example 2
[0132] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0133] In step (a), the heating temperature was adjusted to 77.5° C. and the pressurizing pressure was adjusted to 2.8 MPa.
[0134] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 269 parts and 85 parts respectively.
[0135] In step (c), the stirring speed was adjusted to 330 rpm and the stirring time was adjusted to 2.5 h.
[0136] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0137] Comparative Example 3
[0138] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0139] In step (a), the heating temperature was adjusted to 79.0°C and the pressurizing pressure was adjusted to 2.4 MPa.
[0140] In step (b), 1-butene and 2-ethylhexyl methacrylate are taken in 100 parts and 6 parts respectively.
[0141] In step (c), the stirring speed was adjusted to 325 rpm and the stirring time was adjusted to 2.6 h.
[0142] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0143] Comparative Example 4
[0144] A method for preparing a non-fluorine composite material, which differs from Example 1 in that:
[0145] In step (a), the heating temperature was adjusted to 76.0°C and the pressurizing pressure was adjusted to 3.5 MPa.
[0146] In step (b), 1-butene and 2-ethylhexyl methacrylate were taken in 517 parts and 291 parts respectively.
[0147] In step (c), the stirring speed was adjusted to 325 rpm and the stirring time was adjusted to 2.2 h.
[0148] A method for preparing a battery separator, which differs from Example 1 in that the spraying flow rate and the rotor rotation speed are adjusted to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0149] Comparative Example 5
[0150] A method for preparing a battery separator comprises the following steps:
[0151] Take 15 parts of PVDF with a secondary particle size D50 of 5.0 μm, 85 parts of deionized water, 0.08 parts of sodium carboxymethyl cellulose and 0.8 parts of polyacrylate, mix and stir evenly, and spray the mixed slurry on the lithium battery diaphragm by spraying, adjusting the spray flow rate and rotor rotation speed, and dry it to obtain a surface density of 0.55 g / m 2 of coated diaphragms.
[0152] Experimental example
[0153] 1. Glass transition temperature test, particle size test
[0154] The materials in each embodiment and comparative example were tested for glass transition temperature and particle size, and the tests were as follows:
[0155] Tg test: dry the matrix material emulsion or unit material emulsion, weigh 5-10 mg sample, and test Tg by differential scanning calorimetry. Test equipment: METTLER DSC3, test temperature range: -80-200℃, heating rate: 8℃ / min. After the test, integrate the test curve to obtain the glass transition temperature of the test sample.
[0156] Particle size test: Take the matrix material emulsion, unit material emulsion and non-fluorine composite material emulsion respectively, add a little dispersant, stir, and use Malvern 3000 to test the particle size of the adhesive. The test refractive index is 1.52, the absorption rate is 0.1, and the shading rate is 5% to 20%. The particle size d1 of the matrix material, the particle size d2 of the unit material, and the particle size d3 of the non-fluorine composite material are tested. η calculation: η=(d2-d1) / d2.
[0157] The test results are shown in Table 1.
[0158] Table 1 Glass transition temperature test, particle size test and η calculation results
[0159]
[0160]
[0161] From the test results in Table 1, it can be seen that in the non-fluorine composite materials obtained by the methods of various embodiments of the present invention, the ratio η of the coating layer thickness to the unit material particle size and the glass transition temperature Y of the second polymer satisfy the relationship: Y=100η-46.
[0162] Characterization of glass transition temperature: The glass transition temperature of the matrix material and the non-fluorine composite material in Example 1 was tested. Figure 4 and Figure 5 , Figure 4 This is the test curve of the glass transition temperature of the matrix material emulsion, and the test result is about 98°C; Figure 5This is the test curve of the glass transition temperature of the non-fluorine composite material emulsion. There are two glass transition temperatures, one is 98°C and the other is about -5°C.
[0163] 2. Performance test results of battery separators
[0164] Permeability growth rate test: Permeability growth rate = (coated membrane permeability - base membrane permeability) / base membrane permeability × 100%, where permeability refers to the time required for 100 mL of gas to pass through a fixed area membrane.
[0165] Coverage test: The coverage of the spray coating was tested using a fully automatic coverage tester ZYGD-6040FLC (Guangzhou Zhongyi Optoelectronics Technology Co., Ltd.). The annular light source was adjusted to 3500K white light. 15 points were randomly tested, each with a size of 60×40mm. The average value was taken as the coverage of the sprayed diaphragm.
[0166] Determination of the distance L between the Q coating and the M coating: any dot coating with a particle size greater than 100 μm is set as the Q coating, and the dot coating with the shortest distance to the Q coating is set as the M coating. Use the fully automatic coverage detector ZYGD-6040FLC (Guangzhou Zhongyi Optoelectronics Technology Co., Ltd.) to photograph the surface morphology of the coating diaphragm, select particles with a particle size greater than 100 μm, test the shortest distance between any two adjacent particles, repeat the test 15 times, and take the average value as the final result.
[0167] Coating and electrode adhesion test: The battery separator and electrode sheet (the electrode sheet is a positive electrode sheet, composed of 91 parts of lithium iron phosphate + 3.2 parts of conductive carbon black + 5.8 parts of PVDF with a melting point of 148°C) are cut into 2cm×10cm strips. The coating surface of the electrode sheet corresponds to and overlaps with the coating surface of the separator. The parameters of the hot press are adjusted for dry pressing: cold pressing treatment and hot pressing treatment. Cold pressing conditions: 5MPa, 3min, low temperature 26°C, hot pressing conditions: 5MPa, 3min, high temperature 80°C; the dry pressed sample is peeled off along the long side direction by a 180° peeling method, with a peeling speed of 50mm / min, and finally the adhesion between the coated separator and the electrode sheet is obtained.
[0168] Ionic conductivity performance: In an argon glove box, the membrane was made into a 2016 button battery, and an appropriate amount of electrolyte (EC:PC:DEC = 3:3:1, 0.8Mol / L LiPF6) was added. The AC impedance test in the electrochemical workstation showed that σ = L / (Rb×A), where σ is the ionic conductivity (mS / cm); L is the thickness of the membrane (cm); Rb is the intrinsic resistance of the membrane (Ω); A is the effective area (cm 2 ).
[0169] Battery cell performance evaluation: The coated diaphragm and the ternary positive electrode and graphite negative electrode are wound together. After winding, the battery cells are prepared by hot pressing and cold pressing respectively. The hot pressing and cold pressing processes keep the pressure and time unchanged and only the temperature is adjusted. The hot pressing temperature is 80°C and the cold pressing temperature is 26°C. After the battery cell is prepared, the expansion coefficient and capacity retention rate of the battery cell are tested.
[0170] Expansion coefficient: The battery cell is sealed and stored at high temperature of 60℃ for 10 days, and the battery thickness expansion coefficient is tested. Expansion coefficient = thickness after sealing and swelling for 10 days / thickness when sealed.
[0171] Capacity retention rate: The battery is cycled 800 times at 0.2C charge and discharge, and the capacity before and after the test cycle is: capacity retention rate = capacity after cycle / capacity before cycle.
[0172] The performance test results of the battery separator are shown in Table 2.
[0173] Table 2 Performance test results of battery separator
[0174]
[0175]
[0176] As can be seen from Table 2, the battery separator of the present invention adopts the above-mentioned non-fluorine composite material, and controls the distance L between the Q coating and the M coating to satisfy 100μm≤L≤350μm, which is beneficial to improving the comprehensive performance of the separator, the coating has good overall air permeability, the separator has strong adhesion to the electrode, and the difference in high temperature and low temperature adhesion is not large. After being made into a battery cell, it is not easy to bulge, and the coated separator has good ionic conductivity.
[0177] The coverage of the coated diaphragm is reduced. At the same surface density of spraying, the thickness increases, the distance L increases, the effective bonding area between the battery diaphragm and the electrode sheet decreases, the dry pressing bonding force decreases, and the battery core is easy to expand, which ultimately leads to a decrease in cycle performance; the coverage of the coated diaphragm is increased, and at the same surface density of spraying, the thickness decreases. The shortest average distance L between any two adjacent points of particles larger than 100 μm is smaller, the effective bonding area between the sprayed diaphragm and the electrode sheet increases, and the dry pressing bonding force increases. However, at this time, there is no effective space for the polymer to swell, the battery core is easy to expand, and a larger coverage rate easily affects the passage of lithium ions, resulting in a decrease in ionic conductivity, and ultimately leads to a decrease in cycle performance, such as Comparative Examples 1 and 2;
[0178] In non-fluorine composite materials, the total thickness of the coating layer accounts for too low a proportion, the adhesion between the battery separator and the electrode sheet is significantly reduced, the battery cell is easy to expand, and the cycle performance is low; the total thickness of the coating layer of the non-fluorine composite material accounts for too high a proportion, the hot pressing bonding between the battery separator and the electrode sheet is still good, but due to the increase in the glass transition temperature of the shell layer, the cold pressing adhesion between the battery separator and the electrode sheet is significantly reduced, and the performance difference between the hot pressing and cold pressing processes is large. On the other hand, the increase in the thickness of the coating layer means that the matrix particle size needs to be reduced, which may lead to no effective space for the polymer to swell after the battery separator electrode sheet is dry-pressed, which may easily lead to battery expansion. At the same time, the polymer may easily block the pores of the separator and hinder the passage of lithium ions, resulting in a decrease in ionic conductivity, such as Comparative Examples 3 and 4.
[0179] In Comparative Example 5, the battery separator uses PVDF as the adhesive between the separator and the electrode sheet. The adhesion between the coated separator and the electrode sheet is relatively small, and the performance of the battery cell is far inferior to the battery separator of the present invention. At the same time, PVDF has almost no adhesion to the electrode sheet under low temperature conditions, so the performance of the battery cell prepared by the cold pressing process is very poor.
[0180] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A battery separator, comprising a substrate layer and a discontinuous dot coating on at least one side of the substrate layer; the dot coating comprises a non-fluorine composite material and an adhesive material; The non-fluorine composite material comprises an aggregate of several unit materials, wherein the unit materials comprise a substrate and a coating layer located on the surface of the substrate, the substrate comprises a first polymer, and the coating layer comprises a second polymer; The ratio η of the thickness of the coating layer to the particle size of the unit material and the glass transition temperature Y of the second polymer satisfy the relationship: Y=100η-46, where, η is 25% to 46%; The difference between the glass transition temperature X of the first polymer and the glass transition temperature Y of the second polymer satisfies: XY≥95°C.
2. The battery separator according to claim 1, characterized in that: In the dot coatings, any dot coating with a particle size greater than 100 μm is defined as a Q coating, the dot coating with the shortest distance from the Q coating is defined as an M coating, and the distance L between the Q coating and the M coating satisfies: 100 μm≤L≤350 μm.
3. The battery separator according to claim 1, characterized in that: The difference between the glass transition temperature X of the first polymer and the glass transition temperature Y of the second polymer satisfies: 95°C≤XY≤125°C; And / or, the particle size D50 of the non-fluorine composite material is 4 to 6 μm; And / or, the particle size D50 of the unit material is 0.40-0.60 μm; and / or, the first polymerizable monomer of the first polymer comprises one or more of methyl methacrylate, methacrylonitrile, 2-ethylhexyl methacrylate, methacrylonitrile, ethyl methacrylate, butyl methacrylate, styrene and acrylonitrile; And / or, the second polymerizable monomer of the second polymer includes one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, 1-butene, isooctyl acrylate, butyl methacrylate and 2-ethylhexyl acrylate.
4. The battery separator according to claim 1, characterized in that: The mass ratio of the non-fluorine composite material to the bonding material is 100:(3-8); and / or, the adhesive material comprises at least one of styrene-butadiene rubber, polyacrylate, polystyrene, polymethyl styrene, polyacrylonitrile and epoxy resin; And / or, the dot-shaped coating further includes a stabilizer; the mass ratio of the non-fluorine composite material, the adhesive material and the stabilizer is 100:(3-8):(0.3-0.8).
5. The battery separator according to claim 1, characterized in that: The coverage rate of the dot-shaped coating on the surface of the substrate layer is 10% to 20%.
6. The battery separator according to claim 1, characterized in that: The bonding force between the battery separator and the electrode sheet under the conditions of 5MPa, 26°C and cold pressing for 3min is F1, and the bonding force between the battery separator and the electrode sheet under the conditions of 5MPa, 80°C and hot pressing for 3min is F2. F1 and F2 satisfy the relationship: (F2-F1) / F1<20%.
7. The method for preparing a battery separator according to any one of claims 1 to 6, characterized in that: The following steps are involved: mixing the non-fluorine composite material emulsion and the bonding material to obtain a mixed slurry; The mixed slurry is coated on at least one side of the substrate layer to form a discontinuous dot coating, and the battery separator is obtained after drying.
8. The method for preparing a battery separator according to claim 7, characterized in that: The method for preparing the non-fluorine composite material emulsion comprises the following steps: Conducting a first polymerization reaction on a first emulsifier, a first polymerizable monomer, a first initiator and a first solvent to obtain a first system containing matrix particles; The first system and the second solvent are mixed and subjected to a first ultraviolet irradiation, and then mixed with the second system, the second polymerization monomer and the second initiator and subjected to a second polymerization reaction to obtain a second system containing unit materials; The second system is mixed with salts, subjected to second ultraviolet irradiation, and then mixed with a second initiator to obtain an emulsion containing the non-fluorine composite material.
9. The method for preparing a battery separator according to claim 8, characterized in that: The first polymerization reaction specifically includes: pre-mixing a portion of the first emulsifier, a portion of the first polymerization monomer, a portion of the first initiator and a portion of the first solvent, and then adding the remaining first emulsifier, the first polymerization monomer, the first initiator and the first solvent to carry out a polymerization reaction; And / or, the first ultraviolet irradiation time is 20 to 40 minutes; And / or, the second external irradiation time is 5 to 15 minutes; And / or, the mixed slurry further comprises a stabilizer.
10. A battery, characterized in that: A battery separator comprising the battery separator according to any one of claims 1 to 6.
Citation Information
Patent Citations
PVDF-coated lithium-ion battery separator and preparation method thereof
CN105552277A
Cited By
Non-fluoropolymer, non-fluoropolymer composite diaphragm and application
CN121307424A
Non-fluorine coating diaphragm, preparation method thereof and secondary battery
CN121709861A
A non-fluorine-coated separator and a method for manufacturing the same, a secondary battery
CN121709861B